2020
DOI: 10.1051/0004-6361/201936620
|View full text |Cite
|
Sign up to set email alerts
|

Stellar laboratories

Abstract: IX. New Se v, Sr ivvii, Te vi, and I vi oscillator strengths and the Se, Sr, Te, and I abundances in the hot white dwarfs G191−B2B and RE 0503−289 ⋆,⋆⋆,⋆⋆⋆ ABSTRACT Context. To analyze spectra of hot stars, advanced non-local thermodynamic equilibrium (NLTE) model-atmosphere techniques are mandatory. Reliable atomic data is crucial for the calculation of such model atmospheres.Aims. We aim to calculate new Sr iv-vii oscillator strengths to identify for the first time Sr spectral lines in hot white dwarf (WD) s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Secondly, the recent discovery of spectral lines emitted by heavy elements (Cu, Zn, Ga, Ge, As, Se, Br, Kr, Sr, Sn, Te, I, etc.) in the ultraviolet (UV) spectra of hot DO white dwarfs such as HD 149499B, PG 0109+111, RE 0503−89 (Werner et al 2018;Rauch et al 2020). These astrophysical objects were known before as composed only in hydrogen and helium.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the recent discovery of spectral lines emitted by heavy elements (Cu, Zn, Ga, Ge, As, Se, Br, Kr, Sr, Sn, Te, I, etc.) in the ultraviolet (UV) spectra of hot DO white dwarfs such as HD 149499B, PG 0109+111, RE 0503−89 (Werner et al 2018;Rauch et al 2020). These astrophysical objects were known before as composed only in hydrogen and helium.…”
Section: Introductionmentioning
confidence: 99%
“…Many recent works (Werner et al 2012;Werner et al 2018a;Werner et al 2018b) have shown the existence of spectral lines emitted by heavy elements in the UV spectra of hot DO white dwarfs. Up to now, 18 trans-iron elements (Z ≥ 30) have been identified in the RE 0503-289 star (Rauch et al 2020), which is a hot DO-type white dwarf. A fur-ther eight trans-iron elements (Zn, Ga, Ge, Se, Sr, Sn, Te, I) were found in PG 0109+111 (Hoyer et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These models should contain opacity of heavy elements. In the meantime, 18 trans-iron elements with atomic numbers in the range 𝑍 = 29 − 56 were detected in the RE 0503−289 hot white dwarf (WD) stars (Rauch et al (2020). Recently, Rauch et al (2017b) detected several heavy elements in hot white dwarfs (Se V, Sr V, Te VI and I VI).…”
mentioning
confidence: 99%